Perbandingan Tindak Pidana Makar dalam KUHP Indonesia, Malaysia, Austria dan Konsep Hukum Islam - Silfiah, Rossa Ilma (Universitas Negeri Malang, 2021)
This study aimed to analyze the forms of treason and a comparison of the criminal acts of treason against the Indonesian, Malaysian, Austrian, and Indonesian Criminal Codes and the concept of Islamic law. The research used a normative law with a statutory approach and a comparative approach. The research data were analyzed descriptively. The results of this study found that forms of treason included treason that attacked the legal interests of the head of state, territorial integrity, and government. The crime of treason in Indonesia was distinguished between crimes against security within the country and outside the country, both committed by diplomats and the military. Sanctions for perpetrators of the crime of treason in Malaysia range from the threat of capital punishment, imprisonment, and fines. The crime of treason in Austria did not affect the sentence and did not distinguish between crimes against justice and against the government, all those involved in treason were sentenced to death. The concept of Islamic law provided an extraordinary warning for perpetrators of treason against the government because state security greatly determined the smooth running of worship and the welfare of all citizens.